Vampires and the Undead - Anita Ganeri; Illustrated by David West (London Hachette Children's Books, 2010)
Explores the history of belief in vampires and other undead creatures, describes their features, and discusses vampire lifestyle, Count Dracula, and other topics.
Include Color Illustrations, Glossary and Index
Keywords: Vampires -- Zombies -- Ghosts